Are young female basketball players adequately prepared for a force-velocity jumping and sprinting assessment? - Rial-Vázquez, J.; Nine, I.; Rúa-Alonso, M.; Fariñas, J.; Fernández-Seoane, R.; Jiménez-Reyes, P.; Fernández-del-Olmo, M.; Iglesias-Soler, E. (Pediatric Exercise Science, 2024)
Purpose: The aim of this study was to explore the interday reliability of mechanical variables obtained from the horizontal and vertical force-velocity (FV) profiles in adolescent female basketball players. If found to be reliable, the associations between FV parameters (theoretical maximal force, velocity, and power), squat jump (SJ) height, 30-m sprint, and change of direction (COD) times were evaluated.